ANALYSIS OF PESANTREN ECONOMIC EDUCATION VALUES AT PONDOK MODERN AL-RIFA'IE GONDANGLEGI MALANG - Azizah, Irva (International Education Trend Issues, 2023)
The writing of this article aims to provide an analysis of the values of pesantren economic education as seen through the study of santri behavior in managing finances and consumption. A qualitative approach with a case study type is used in this article. Data collection through observation, in-depth interviews, and documentation of several boarding school rules and santri expenditure records. While the analysis method, uses Creswell's data analysis process. The object of research is female and male students of Pondok Modern Al-Rifaie Gondanglegi Malang. After examining the attitudes and behavior of financial management and examining the attitudes and behavior of santri consumption, the values of pesantren economic education that are instilled in the santri of Pondok Modern Al-Rifaie Gondanglegi can be found. Among them is the value of simplicity instilled through the habituation of frugal living from ustadzah and role models from caregivers, then the value of independence that is embedded automatically seen from the independence of students to have personal savings, as well as the value of responsibility that is embedded because it carries the mandate of being a senior room where it requires modeling its room children to live frugally.